Are you getting full benefits from the use of social media? A review combining the concepts of social media, social capital and knowledge sharing - Santos, Rosangela Fritscher; Oliveira, Mirian; Chaves, Marcirio Silveira (Revista de Administração da UFSM, 2021)
Purpose - The social media have become powerful tools that can be used to do much more than connecting relatives and friends, helping find a job or providing advertising space. This study aims to present the benefits of combining the subjects related to Knowledge Sharing, Social Media and Social Capital theory. Design/methodology/approach – Literature review of 22 papers identified as relevant when combining the subjects Social Media, Social Capital and Knowledge Sharing. The 22 documents were subjected of content analysis. Findings – The analysis of the literature revealed two fundamental roles for social media within organizations – an operational role – working as a channel or tool; a transformative role – used to support organizational strategy. Research limitations/implications - The limitation of this study is related to the limited number of papers that resulted from the search. Practical implications – The benefits of combining the three subjects include improvements on informal communication, better collaboration and cooperation, and a positive influence on job performance and innovation. Originality/value - The proposed research agenda highlights the importance of future investigations into the sharing of tacit knowledge through Social Media; focusing on how to generate trust via Social Media and suggests research attention related to knowledge protection.